Indicators of physical activity of people with motor disabilities associated with their life satisfaction and attitude towards one’s disability - Radzevičienė, Liuda; Miliūnienė, Lina; Gudonis, Vytautas (Special Education, 2018)
The research is dedicated to find out possible indicators of physical activity of people with motor disabilities associated with their life satisfaction and attitude towards one’s disability. It was set that people with motor disability participating in the sports activities feel satisfied in comparison to those who used to be passive. Physical activity of persons who have motor impairments is caused by several reasons that are associated with personal and environmental factors. 162 adults after trauma of spincord and are in wheelchairs participated in the research.